Twinning and Ovulation Rate for Sustainable Production in Cattle - Kamalludin Mamat Hamidi; Anjas Asmara Samsudin; Suyadi Suyadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
Profits is very important in most industries and determined by the cost and amount of products generated. In the livestock industries, higher number of viable animals produced will improve the economies of scale, hence, their profit. In general, twinning can be a good approach to increase reproductive capacity, and consequently the production volume. Cattle are monovular animal, typically give birth to one offspring and multiple birth is rare. Multiple gestation is mostly unfavorable in the dairy industry due to their negative impact on reproductive and production performance on cow and calf. Twinning is highly correlated to ovulation rate and various genes that are affecting hyperprolificacy in sheep have been identified. Many studies have reported quantitative trait loci (QTL) that are associated with high ovulation rate and twinning in cattle. Besides the genetic factor, twinning can also be induced via hormonal methods. Knowledge on the factors that causing hyperprolificacy can assist the breeders or farmers for their selection, based on their objectives and strategy.